Una construcción posible de la identidad latinoamericana (Aprender a ser) - Aubry, Kenia (Romanica Silesiana)
The present article reflects on theories of decolonization and the urgency of border, peripheral or third world countries to learn how to be; that is, to decolonize themselves of the internal colonialism that emerges with the rise of nation-states: one that only archives the resemantization of colonialism of power, and emphasizes the colonial difference. The paper also reflects upon the epistemic difference that, since the Boom, has marked the literary discourse, as it examines Renato Prada Oropeza’s novel, While the Night Falls, as a decolonizing text which narrates Hugo Banzer’s military coup in Bolivia. Key words: Decolonization, learning how to be, difference, epistemic, memory.